Wave energy harvesting based on multilayer beads integrated spherical TENG with switch triggered instant discharging for self-powered hydrogen generation - Zhang, Wang; He, Wencong; Dai, Shuge; Ma, Fuxue; Lin, Pei; Sun, Junlu; Dong, Lin; Hu, Chenguo (Nano energy, 2023)
Effective strategies to gain hydrogen energy from harvesting and conversion from ocean energy attract extensive attention in the new energy source field. Remarkably, triboelectric nanogenerator (TENG) presents potential applications for harvesting large-scale blue energy from the ocean. Herein, we propose a self-powered hydrogen generation system by multilayer beads integrated spherical TENG with the power management system (PMS). The triggered switch used in the spherical TENG overcomes the limitation of working frequency through instantaneous driving, significantly improving the output performance and greatly expanding its application range. The six-layer beads integrated TENG presents a significant improvement in converting water wave energy into electric energy, and its power density reaches 21.3 W m−3 at 2 Hz. The integrated TENG charges 470 μF capacitor to 5 V in 200 s, and the hydrogen production rate is about 64.5 μL min−1 under the water wave condition, which overcomes the limitation of external power demands for conventional water electrolysis. Compared with the electrochemical cells driven by solar, our integrated system can operate in all weather conditions without an external power source. This work demonstrates the feasibility of the electrochemical conversion of low-frequency water wave energy into green energy. [Display omitted] •An instantaneous discharging TENG with ultrahigh output power is demonstrated by integrating a self-controlled switch.•The ID-TENG presents the excellent capability of harvesting ocean wave energy.•A self-powered water electrolysis system is demonstrated for highly efficient hydrogen production.